2023
DOI: 10.1186/s12870-023-04258-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined transcriptomic and metabolomic analyses elucidate key salt-responsive biomarkers to regulate salt tolerance in cotton

Mingge Han,
Ruifeng Cui,
Delong Wang
et al.

Abstract: Background Cotton is an important industrial crop and a pioneer crop for saline-alkali land restoration. However, the molecular mechanism underlying the cotton response to salt is not completely understood. Methods Here, we used metabolome data and transcriptome data to analyze the salt tolerance regulatory network of cotton and metabolic biomarkers. Results In this study, cotton was stressed at 400 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Various studies have shown that plant hormones play a crucial role in regulating plants' adaptive growth under stress conditions. Transcriptomic and metabolomic analyses under salt stress in cotton have revealed that ABA is a key salt-responsive biomarker for salt tolerance [34]. Jasmonic acid (JA) also influences plant responses to non-biological stresses such as salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that plant hormones play a crucial role in regulating plants' adaptive growth under stress conditions. Transcriptomic and metabolomic analyses under salt stress in cotton have revealed that ABA is a key salt-responsive biomarker for salt tolerance [34]. Jasmonic acid (JA) also influences plant responses to non-biological stresses such as salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…As a comparison, one control variety of Gossypium hirsutum (Zhong 9807) known for its high salt tolerance [ 105 ] was obtained from the gene bank of the Cotton Research Institute, Chinese Academy of Agricultural Sciences (CRI, CAAS) in Anyang (36.1 N, 114.33 E), Henan province, China. Professor Wuwei Ye identified the salt tolerance characteristics of the control variety Zhong 9807, which have been widely exploited in various research studies [ 106 , 107 , 108 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it serves as a valuable material for investigating the molecular mechanisms underlying plant salt tolerance and isolating salt tolerance genes. These genes can offer insights into plants’ strategies for adapting to salt stress [ 25 , 26 , 27 ]. With the rapid advancement of cotton genome research, several functional genes involved in the response to salt stress have been identified [ 8 ].…”
Section: Introductionmentioning
confidence: 99%